Donor-acceptor interactions of iodine with pyridine bases in aqueous and organic media - Shubina E. N.; Flick E. A.; Zhukova I. Yu. (BIO Web of Conferences)
Spectrophotometric studies were carried out on the possibility of the formation of complexes between active forms of iodine and pyridine bases in solvents of different polarities - water (H2O) and dichloromethane (CH2Cl2). Analysis of electronic absorption spectra showed the appearance of different forms of iodine when dissolved in H2O (220 nm, 290 nm, 360 nm, 460 nm) and in CH2Cl2 (240 nm, 300 nm, 504 nm). To prove the possible interaction of various forms of iodine with pyridine bases, absorption spectra of pyridine, 2,6-lutidine, collidine and mixtures (iodine-pyridine base) in H2O and CH2Cl2 were obtained. It has been established that pyridine bases are capable of stabilizing iodine and iodonium ions in the form of donor-acceptor complexes. This is confirmed by intense and wide absorption bands in the spectral region of 250–300 nm (H2O) and 250–450 nm (CH2Cl2), which is associated with charge transfer and the formation of donor-acceptor type complexes, for example, [PyI2] and [PyI]+. The stability constants (K) of the complexes were determined in CH2Cl2. In accordance with the obtained spectral and calculated data, the iodine-pyridine complex is the most stable (K = 0.45 l/mol) compared to similar complexes containing pyridine bases with large steric effects. Among the complexes formed between the iodonium ion and pyridine bases, the most stable was the complex of the iodonium ion with collidine (K = 22 l/mol).